You can lead a horse to water . . . what Self-Determination Theory can contribute to our understanding of clinical policy implementation - Smith, G.; Williams, Theresa (The Royal Society Medicine Press Ltd, 2016)
There has been increasing reliance on policy directives as instruments for shaping clinical practice in health care, despite it being widely recognized that there is a significant translation gap between clinical policy and its implementation. Self- Determination Theory, a widely researched and empirically validated theory of human needs’ fulfilment and motivation, offers a potentially valuable theoretical framework for understanding not only why the current policy environment has not led to the anticipated improvement in the quality and safety of clinical care but, importantly, also provides guidance about how organizations can create an environment that can nurture behavioural change in the workforce. We describe an alternative approach to clinical policy-making underpinned by Self-Determination Theory, which we believe has broad application for the science of clinical implementation theory.